Implementation of Flipped Classroom to Improve the Studentâ€™s Learning Result in Senior High School Education, A case study: Senior High School 1 SETU BEKASI, INDONESIA - Syakdiyah, Halimatus; Wibawa, Basuki (International Journal of Engineering and Technology, 2018)
Chemistry lesson is one of the lessons considered difficult, especially in middle school students in Indonesia. This also happens in high schools in Bekasi. This study aims at improving the specific learning outcomes on chemistry subject by applying flipped classroom. The increased learning outcome is measured by comparing learning outcomes using an expository method on the same level. The selection of classes applying the flipped classroom and classes using the expository method is done randomly. From the result of the study, the difference in chemistry learning outcomes between students studied using Flipped Classroom and expository learning strategies. Based on the result of calculation is obtained difference in student learning outcomes between students who learn using the Flipped Classroom strategy and students who learn using the expository strategy.Â Â